Nerve Growth Factor and Pathogenesis of Leprosy: Review and Update - Aarão, Tinara Leila de Souza; de Sousa, Jorge Rodrigues; Falcão, Aline Semblano Carreira; Falcão, Luiz Fábio Magno; Quaresma, Juarez Antônio Simões (Frontiers in Immunology, 2018)
Neurotrophins are a family of proteins that regulate different aspects of biological development and neural function and are of great importance in neuroplasticity. This group of proteins has multiple functions in neuronal cells, as well as in other cellular populations. Nerve growth factor (NGF) is a neurotrophin that is endogenously produced during development and maturation by multiple cell types, including neurons, Schwann cells, oligodendrocytes, lymphocytes, mast cells, macrophages, keratinocytes, and fibroblasts. These cells produce proNGF, which is transformed by proteolytic cleavage into the biologically active NGF in the endoplasmic reticulum. The present review describes the role of NGF in the pathogenesis of leprosy and its correlations with different clinical forms of the disease and with the phenomena of regeneration and neural injury observed during infection. We discuss the involvement of NGF in the induction of neural damage and the pathophysiology of pain associated with peripheral neuropathy in leprosy. We also discuss the roles of immune factors in the evolution of this pathological process. Finally, we highlight avenues of investigation for future research to broaden our understanding of the role of NGF in the pathogenesis of leprosy. Our analysis of the literature indicates that NGF plays an important role in the evolution and outcome of Mycobacterium leprae infection. The findings described here highlight an important area of investigation, as leprosy is one of the main causes of infection in the peripheral nervous system.